A systematic literature review of the experiences and supports of students with autism spectrum disorder in post-secondary education. (July 2017) - Anderson, Anastasia H.; Stephenson, Jennifer; Carter, Mark
Highlights: A comprehensive systematic literature review was conducted of post-secondary experiences and supports of students with ASD. The strengths of students with ASD and the benefits of attending post-secondary education were described. There was a diverse range of social, emotional, and sensory difficulties that negatively impacted their education. Supports provided to post-secondary students were often incongruous with need and produced idiosyncratic benefits. The study demonstrated the need for novel and individualised supports. Abstract: Background: Post-secondary students with ASD experience a range of academic and non-academic difficulties and represent approximately one percent of the post-secondary cohort. The purpose of this review is to conduct a systematic literature review of articles that examined the barriers, challenges, and benefits experienced by post-secondary students with ASD, and the supports and services provided to them, and also to analyze student satisfaction with those supports. Method: Three databases were searched and articles were screened against eligibility criteria. The twenty-three studies (reported in twenty-nine articles) that met criteria were also assessed for quality. Data pertaining to the benefits, challenges, and barriers experienced, and student satisfaction with supports and services provided, were extracted and analyzed. Results: The studies highlighted the diverse range of social, emotional and sensory difficulties experienced by students with ASD, and how those difficulties negatively impacted all aspects of their post-secondary education. Also, the supports provided were often incongruous with need and produced idiosyncratic benefits, demonstrating the need for individualized supports and novel solutions to be identified. Suggestions for future research were made. Conclusions: While prior research on post-secondary students with ASD is limited and geographically circumscribed, the current body of research suggests that students with ASD are often more concerned with non-academic issues than with their academic studies. Also, many post-secondary educational institutions were found proficient at providing traditional academic supports while non-academic supports and resources were often found inadequate. In addition, many students with ASD experienced anxiety or had poor advocacy skills and this impeded their ability to access available supports. Finally, students with ASD were found to be very diverse and to experience idiosyncratic responses to supports, suggesting that supports ideally needed to be individualized, ubiquitous, and continually monitored.